Planning and acquisition of control data to validate forest inventory and the estimation of fuel variables derived from LiDAR data and high resolution CIR images - Tomé, Margarida (2010)
The estimation of forest and fuel variables by using LiDAR data and CIR high-resolution images is the main objective of the project PTDC/AGR-CFL/72380/2006 financed by the Portuguese foundation Fundação para a Ciência e Tecnologia (FCT). To estimate those variables a novel software system needs to be developed and tested. To this end, control data are necessary. In this article it is addressed the planning and acquisition of traditional forest inventory data in pure eucalyptus strata as well as topographic data. The latter is acquired with the classical topographic methods by means of a total station and by using global positioning techniques with the help of high precision GPS receivers.